A congestion-aware and fault-tolerant readout network ASIC for a high-density electrode array targeting at neutrinoless double-beta decay search in a TPC. (1st December 2022) - You, B.; Xiao, L.; Dai, W.; Sun, X.; Mei, Y.; Huang, G.
Abstract: We present a distributed, self-organizing, fault-tolerant and congestion-aware readout network application specific integrated circuit (ASIC) for a high-density electrode array targeting at neutrinoless double-beta decay search in a time projection chamber (TPC). A sensor network is proposed to achieve the readout of the high-density electrode array. This network consists of approximately 1 × 10 5 single-electrode Topmetal-S sensors with a pitch of approximately 5 10 mm. Static routing is implemented in the first version of the sensor network, without the feature of congestion awareness, which means that only one deterministic path is available for a given packet. Because of the limited memory in each sensor, data will be lost when congestion occurs in this first version of the network. Therefore, the network should have congestion awareness to improve its memory occupancy and effective throughput. Accordingly, a 224 × 224 network with congestion awareness is emulated. The simulation results show that better performance of the sensor network can be achieved with less hardware. An ASIC named adaptive and fault-tolerant readout network chip (AFT-RNC) is implemented with 48.2% of the area of the first implementation.